Introduction To Karawitan Daksinaning Nusa Bangsul's Work | Pengantar Karawitan Daksinaning Nusa Bangsul - I Kadek Rai Jaya Triguna (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
This article discusses the creation of Daksinaning Nusa Bangsul's New Tabuh Creations. The birth of the idea in this work was when the stylist wanted to introduce the characteristics of tourism icons in Ungasan Village. The hallmark or icon of Ungasan Village is named Melasti Beach, which is very proud of the Ungasan Village community. Ungasan Village, which has a panoramic view of the beauty of the beach icon, is very interesting to visit; the stylists got a stimulating idea and wanted to elevate the beauty of the atmosphere at Melasti Beach, pouring it into the composition work of New Tabuh Creations entitled Daksinaning Nusa Bangsul. Through this work, the stylist hopes to help introduce wider the Ungasan Village, which typically the population in this village looked at Ungasan as a hot and barren village. But behind that, Ungasan Village has one of the most beaches with an icon that must be visited because it can entertain oneself and provide comfort with treats in Melasti Beach. This beach is unique among the surrounding beaches, having an artificial platform that functions as a place to use for ngayud sekah. In creating the musical works of Nusa Bangsul, the stylist uses the five stihiti ngawi sani method, where the method consists of several stages, including the inspiration stage (ngawirasi), the exploration stage (ngawacak), the conception stage (planning), the execution stage (ngewangun) and the production (ngebah).